The effect of some environmental factors on the density and distribution of freshwater Gastropoda Melanopsis nodosa and M. costata (Ferussac 1823) in the Banks of Shatt Al–Arab, Basrah, Iraq: environmental factors on Melanopsis nodosa and M. costata - Al–Baghdadi, Nada M. (Iraqi Journal of Aquaculture, 2024)
The current research aimed to study the effect of monthly changes on the density and distribution of the two most common snails, Melanopsis nodosa and Melanopsis costata, in five stations in the middle part of the Shatt al-Arab River. It provides us with knowledge of the intertidal area on banks of the Shatt Al-Arab coast that the environment is suitable for the life of these species of snails in the lowest tidal region; these species were found in high densities during months of Spring and Autumn seasons compared with Summer and Winter at all stations, which indicates the effect of the moderation of temperature on the density and distribution of these species. The statistical analysis showed an inverse correlation between the density of snails, salinity, and current waters of the Shatt al-Arab River and a positive correlation between the density with water temperature and pH. However, the excessive rise in water temperatures of the Shatt al-Arab, which was associated with the rise in the concentration of salinity during most of the Summer months as a result of the decrease in water releases, which was originally caused by climate changes and problems with the upstream countries neighboring Iraq, which caused sharp decreases in the densities of individuals of these species.